2014
DOI: 10.6000/1929-7092.2014.03.26
|View full text |Cite
|
Sign up to set email alerts
|

Socially Responsible Investment: A Comparison between the Performance of Sustainable and Traditional Stock Indexes

Abstract: Abstract:The doubt about whether socially responsible investment is a viable strategy for investors seeking to maximize both social and financial returns is the central question of this paper. This is addressed by investigating whether portfolio selection based on sustainability criteria harms investor's returns, or in contrast it can be a driver of superior financial benefits. With this purpose, daily prices and returns of 4 traditional and 10 sustainable stock indexes are analyzed from 2001 to 2011 and in th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
7
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(7 citation statements)
references
References 35 publications
(28 reference statements)
0
7
0
Order By: Relevance
“…Further, conventional investors constantly underestimate the costs of externalities generated by such conventional/non-SRI companies while overestimating the costs of holding responsible companies relative to their benefits (Marsh, 2000). Sufficient literature exists indicating the SRI mutual fund portfolios as well as indices beating the markets during identified economic and market conditions, bolstering the assumption of ‘doing well while doing good’ (Collison et al, 2008; Curto & Vital, 2014; Hill et al, 2007; Hume & Larkin, 2008). The expected returns of SR stocks have been documented to be greater than those of conventional stocks, especially during the crisis period, encouraging higher money flows in the relatively secure and reliable investment funds (Parida & Wang, 2018; Paul, 2017; Nofsinger & Varma, 2014).…”
Section: Literature Reviewmentioning
confidence: 99%
“…Further, conventional investors constantly underestimate the costs of externalities generated by such conventional/non-SRI companies while overestimating the costs of holding responsible companies relative to their benefits (Marsh, 2000). Sufficient literature exists indicating the SRI mutual fund portfolios as well as indices beating the markets during identified economic and market conditions, bolstering the assumption of ‘doing well while doing good’ (Collison et al, 2008; Curto & Vital, 2014; Hill et al, 2007; Hume & Larkin, 2008). The expected returns of SR stocks have been documented to be greater than those of conventional stocks, especially during the crisis period, encouraging higher money flows in the relatively secure and reliable investment funds (Parida & Wang, 2018; Paul, 2017; Nofsinger & Varma, 2014).…”
Section: Literature Reviewmentioning
confidence: 99%
“…As companies are under continued pressure to improve their environmental, social and governance disclosure and performance (Ho, 2013;Kolk, 2008), inclusion in a responsible investment index is becoming more prevalent (Curto & Vital, 2014). Examples of prominent responsible investment indices in the global context include the Domini 400 Social Index, the FTSE4 Good Indices series and the Dow Jones Sustainability Indexes series.…”
Section: Characteristics Of Companies Targeted By Shareholder Activistsmentioning
confidence: 99%
“…Finally, the third hypothesis builds on SRI outperforming conventional investments as investors underestimate the benefits of socially responsible investments relative to their costs (Marsh, 2000). Empirical studies have found SRI mutual fund portfolios as well as indices beating the markets during respective periods, reiterating incentive to the responsible investor (Hill et al, 2007;Hume and Larkin, 2008;Collison et al, 2008;Curto and Vital, 2014). Others found SRI screens earning abnormal positive returns during the crisis period, encouraging higher money flows in the relatively secure and reliable investment funds (Varma and Nofsinger, 2012;Paul, 2017;Parida and Wang, 2018).…”
Section: Literature Reviewmentioning
confidence: 99%